Capitalising on urban cultural resources for creative city development: A conceptual review and the way forward for Malaysia’s George Town - Khoo, Suet Leng; Nurwati Badarulzaman,; Narimah Samat,; Sharifah Rohayah Sheikh Dawood, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
The renewed interest and attention given to cities or urban areas as the catalyst of growth and economic development have garnered importance both in developed and developing countries alike. In advocating sustainable urban development, there is now emphasis on embedding the element of culture in the process of urban planning to spur economic development. As economic globalization triggers and heightens competition amongst cities, many cities in the world are strategizing to leverage on their cities’ cultural assets and resources. Cities are now embracing notions of creativity and innovation into the strategic planning of place, culture and the economy, thus, the birth of the creative city aspiration. This conceptual paper aims to discuss the applicability of the creative city concept for Penang, Malaysia by examining the extent to which cultural capital can be utilized as resources in creative city development, in particular, the challenges and prospects that George Town faces in the quest of a transformation to a full-fledged creative city. It was found that the way forward for this is an orchestrated effort in which government agencies work in collaboration with community leaders, business community, non-governmental organizations (NGO), and other stakeholders to make proposals and recommendations for the earnest transformation of Georgetown into a creative cultural (heritage) city . Development plans should incorporate regenerative cultural projects that cater to community needs with provisions for longitudinal studies to monitor and evaluate the social, economic and environmental impacts of the city’s cultural projects.